Fluoxetine Exposure During Sexual Development Disrupts the Stress Axis and Results in Sex- and Time- Dependent Effects on the Exploratory Behavior in Adult Zebrafish Danio rerio - Vera-Chang, Marilyn N.; St-Jacques, Antony D.; Lu, Chunyu; Moon, Thomas W.; Trudeau, Vance L. (Frontiers in Neuroscience, 2019)
The antidepressant fluoxetine (FLX), generally the first line of pharmacological treatment in adolescents and pregnant women with affective disorders, is an emerging endocrine disruptor that is also released to the environment through sewage. Recently, we demonstrated that FLX exposure during the first 6 days of life in zebrafish (ZF; Danio rerio) induced a male-specific reduction in the exploratory behavior in the adult ZF that was linked to a reduction in cortisol production that persisted across three generations. Here we investigated sex differences in the behavioral and stress responses following FLX (0.54 and 54 μg⋅L–1) exposure during two periods of sexual development in ZF; early (0–15 days post-fertilization, dpf) and late (15–42 dpf). Our findings revealed that the stress response in females was reduced compared to that of males independent of the treatment. We also found that FLX reduced total body cortisol levels in the adult ZF regardless of sex and window of exposure. The hypocortisol phenotype of our FLX-treated fish was associated with behavioral alterations in the adult fish, which depended on the window of exposure; males were more sensitive to FLX during early development whereas females were affected during late development. A sexually dimorphic behavioral response induced by the low cortisol phenotype was observed in the FLX-treated ZF; females had higher exploratory activity whereas the males had reduced behavior. In conclusion, FLX results in sex- and window of exposure-specific effects on the behavioral activities in adult ZF. These findings highlight the importance of sex differences and timing on the long-term effects of antidepressant treatments. Knowledge of the sex-specific effects of antidepressants and the importance of early life exposure to chemical stressors may help us understand the impact of highly prescribed drugs such as FLX on the fetus from FLX-treated pregnant women as well as aquatic species in environments receiving sewage effluents.